Sistem Pendukung Keputusan Pemilihan Saham BUMN dengan Model AHP - Kusuma, Aniek Suryanti; Aryawan, I Made Gitra (INFOTEKS (Information Technology, Computer and Sciences), 2019)
Investing or investing money in the hope of generating long-term profits and in the near future, can be done by investing in stocks. Stock investment in the Indonesia Stock Exchange which is one of the investments with high profit levels. The profit of stock investment is greatly influenced by the selection of the right stocks in a portfolio. However, if one chooses shares in a portfolio, there may be a loss. To avoid these losses investors usually buy liquid BUMN shares on the stock market. The problem that reappears is that not all SOE shares produce significant and sometimes stagnant profits. Analyzing the uncertainty of a stock, investors can involve the stock selection process by using a decision support system. Stock selection with SPK can produce a stock portfolio with a higher level of profit compared to the results of individual decision making. Implementation of the SPK stock selection uses two economic approaches, namely fundamental analysis and technical analysis. Fundamental analysis uses financial ratio data which has a significant influence on a company's stock development. This study uses the AHP method to accommodate the results of individual stock decision making. AHP method is used to rank the best alternative from a number of alternatives. This research produces individual stock ranking which can be used as a stock selection recommendation for investors.